Consumption of intravenous immunoglobulins in Clinical Hospital Center Osijek 2006-2010. Issue 2 (12th March 2012) - Stiblik-Stipesevic, S.; Vukovic, D.
Abstract : Background: Retrospective analysis of the use of intravenous immunoglobulins (IVIG) in our hospital. On the National Drug List The authors find immunoglobulins 0.5 g/10 ml, 2.5 g/50 ml and 5 g/100 ml. Prices were constant during the period 2006-2010, 240 kn/g and 459.6 kn/g. Purpose: To determine the costs of IVIG and the largest consumers (clinics/wards) over a four-year period in the hospital. Materials and methods: Retrospective analysis of data obtained by computer program. Financial costs are given in kunas (1kn=7.5€), and consumption of IVIG in grams. Results: The costs of IVIG were: 257062.09 kn in 2006, 455430.52 kn in 2007, 476072.30 in 2008, 702350.48 in 2009 and 763276.67 in 2010. Total consumption of IVIG in 2006 was 1257 g, 2097g in 2007, 1979.5 g in 2008, 2729 g in 2009 and 3018 in 2010. The largest consumers were Anaesthesiology: 75 g in 2006, 150 g in 2007 and 2.5 g in 2009 and 2010; Immunology: 210 g in 2006, 240 g in 2007, 480 g in 2008, 550 g in 2009 and 580 g in 2010; Haematology: 32.5 g in 2006, 476.5 g in 2007, 131 g in 2008, 130 g in 2009 and 20 g in 2010; Haemodialysis – 2.5 g in 2006, 5.0 g in 2007 and 2008 and 100 g in 2009; Paediatrics: 377 g in 2006, 289 g in 2007, 804.5 g in 2008, 1110.5 g in 2009, 1861 g in 2010; Neurology – 450 g in 2006, 840 g in 2007, 400 g in 2008, 781 g in 2009, 575 g in 2010. Conclusions: In the given period costs for IVIG increased by 270%, while consumption went up by 240%. The largest consumers were the Paediatrics Clinic, Allergology and Immunology, followed by the Neurology Clinic, whose consumption oscillated. The Anaesthesiology and Haematology wards consumed decreasing amounts of IVIG.